The Influence of Competency Development and Performance on the Professionalism of Civil Servants (ASN) in the Padang Lawas Regency Government - Fitri Yani Lubis; Ali Mukti Tanjung; Didin Muhafidin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the influence of competency development and performance on the professionalism of Civil Servants (ASN) in the Padang Lawas Regency Government both partially and simultaneously. The population of this study consists of all ASN employees in the Padang Lawas Regency Government, with a sample size of 100 people. The data analysis method is quantitative, using SPSS Version 23. The results of the study are as follows: 1). Based on the hypothesis test, it can be explained that competency development has a significant effect on employee professionalism in the Padang Lawas Regency Government. The influence of competency development on employee professionalism is 40.6%, indicating a significant effect. 2). Based on the hypothesis test, it can be explained that performance significantly affects employee professionalism in the Padang Lawas Regency Government, with the influence of performance on employee professionalism at 42.7%. 3). Based on the hypothesis test, the combination of competency development and performance together significantly affects employee professionalism in the Padang Lawas Regency Government by 57.1%. The remaining 42.9% is influenced by other factors or variables not included in the research model.